Enteroclysis in obscure gastrointestinal system hemorrhage of small bowel origin* - Uğur KORMAN; Fatih KANTARCI; Doğan SELÇUK; Serap ÇETİNKAYA and Sebuh KURUĞOĞLU and İsmail MİHMANLI (Turkish Journal of Gastroenterology, 2019)
-